1970
DOI: 10.1063/1.1653410
|View full text |Cite
|
Sign up to set email alerts
|

Barium Manganese Fluoride, a New Crystal for Microwave Ultrasonics

Abstract: Frequency and temperature dependence of the microwave elastic properties and the velocities of propagation are reported for BaMnF4. A sharp anomaly in attenuation indicates that a crystallographic phase transition occurs at T=255°K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1975
1975
2006
2006

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…And even when they do signal a phase transition, its nature is not revealed in any direct way. A rather good example in ferroelectrics is the work of Spencer and Kominiak [6] on the antiferroelectric incommensurate transition in BaMnF 4 [7,8]. Their ultrasonic data were for some years the only evidence of a phase transition, and such skepticism surrounded these data that they were not cited in subsequent work on BaMnF 4 from the same laboratory.…”
Section: Ultrasonic Techniquesmentioning
confidence: 95%
“…And even when they do signal a phase transition, its nature is not revealed in any direct way. A rather good example in ferroelectrics is the work of Spencer and Kominiak [6] on the antiferroelectric incommensurate transition in BaMnF 4 [7,8]. Their ultrasonic data were for some years the only evidence of a phase transition, and such skepticism surrounded these data that they were not cited in subsequent work on BaMnF 4 from the same laboratory.…”
Section: Ultrasonic Techniquesmentioning
confidence: 95%
“…The melting temperatures range between 720 and 965°C; the Curie-Weiss temperatures can be extrapolated from the temperature dependence of the dielectric constants and range between 810 and 1320°C. 11 In BaMnF 4 an additional structural phase transition occurs at ϳ255 K. 12 The resulting low-temperature structure is incommensurate along the c axis. 13 To facilitate a systematic comparison between the different BaMF 4 systems we do not consider this low-temperature structure of BaMnF 4 in the present study and instead use perfect Cmc2 1 symmetry for all systems.…”
Section: Introductionmentioning
confidence: 99%
“…For a(T)> 0 the equilibrium of the system is at Qi 0= #2 0==0 > while for «(T)<0 there are two possible situations depending on the relative magnitudes ofb 1 …”
mentioning
confidence: 97%
“…1 Ryan and Scott 2 investigated the transition by Raman scattering and showed that it is antiferrodistortive and involves a doubling of the unit cell. Recently the author 3 reported ultrasonic velocity measurements for the pure modes propagating along the principal axes and showed that there are sharp velocity dips for the longitudinal mode propagating along the c axis (v cc ) and for the shear mode propagating along the c (orb) axis and polarized along the b (or c) axis {v ch = v bc ).…”
mentioning
confidence: 99%
See 1 more Smart Citation